UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BIJI BUAH DURIAN (Durio zibethinus Murr) DENGAN MENGGUNAKAN METODE DPPH ANTIOXIDANT ACTIVITY TEST OF ETHANOL EXTRACT FROM Durio zibethinus Murr SEEDS BY DPPH METHOD - Farida Amir; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2014)
Durian fruit already famous enough in Indonesian society. Not only the content of the fruit, but Durian also have many advantage for example the seed, leather, root and the leaves that useful for human healthy. Then, phytochemical screening test and antioxidant activity test. Antioxidant activity test use scavenging test to 2,2-diphenyl-1-picryhidrazil (DPPH) radical. On antioxidant activity test, mix of extract and DPPH are incubate for 30 minutes, then the absorbance is measured on λ = 514 nm using spectrophotometer. The absorbance from sample, blank, and negative control are converted as Antioxidant Activity Absorbance (AA%). Based on result of phytochemical ethanol extract, Durian steud contain of fenolic, flavonoid, alkaloid, and tryterpenoid. Based on antioxidant activity test with DPPH radical scavenging method by spectrophotometer. Ethanol extract of Durian has antioxidant activity about EC 50 23,10 μg/mL and Vitamin C as comparison has antioxidant about EC 50 3,76 μg/mL. Keywords: Durian seed, phytochemical, antioxidant activity, DPPH